Between cultural and natural heritage: pluralism in planning tourism products for rescuing “the lost (Ogoja) province”, north-central Cross River State, Nigeria - Ingwe, Richard (Journal for Geography, 2014)
The planning of tourism products in the north-central Cross River State (corresponding to ‘old Ogoja province) is examined in this study. Explained in the article are: justification of the need for undertaking community-based tourism development strategy as a means of reducing inter-regional disparity in development aroused by historical discrimination against the region through eras of Trans-Atlantic Slave Trade, colonialism, and successive post-independent governments; creation of special development funds aimed at addressing challenges posed by personalization of government thereby creating governance deficits; and descriptions of the tourism potentials/resources of the north-central Cross River State. Rather than adopting the advice of tourism experts in the 1960s that African countries ought to prefer to design cultural-heritage tourism products aiming towards attracting some 145 million tourists from the United States of America (USA) who might be satiated with natural heritage tourism products offered back home. Here, it is argued here that considering myriad socio-economic-political dynamics thereafter –including anti-African/Nigerian political measures such as barring US citizens from visiting Nigeria or parts of it- there is no need concentrating on such restricted tourism products. This is justified by the fact that with nearly 170 million population –most of whom are expecting to move from poverty towards the middle class among other prosperous economic statuses and who do not need to immediately access foreign natural heritage tourism, there is need for north-central Cross River State –a region possessing diverse tourism resources to plan tourism products that seek to integrate natural heritage with the cultural varieties in order to properly capture both local and foreign tourists. Foreign tourists here covers a larger spectrum beyond US visitors including visitors from large and increasing number of member states of the United Nations.